NARRATIVE POLICY ANALYSIS : TRADE OFF PELAYANAN DAN PENGAWASAN DI ERA POST BORDER - Apriansyah, Tofa; Purwadianto, Agus; Hanita, Margaretha (JURNAL PERSPEKTIF BEA DAN CUKAI, 2020)
ABSTRACT:The XV Economic Policy Package has created a gap between control tasks and ease of doing business. This study aims to determine the narrative differences in the implementation of The XV Economic Policy Package, especially in simplifying the import trade system and analyzing strategic changes in the business process of Drug and Food Control. The Narrative Policy Analysis (NPA) is used in this study to analyze at the meso (group/organization) level using interviews with Indonesian-FDA and DGCE Officers. The study is focusing on the narrative of the President of the Republic of Indonesia and the response of the Indonesian-FDA and DGCE Officers who play roles in implementing the controls. Metanaration that appears as a solution analysis is "an effort to reduce dwelling time and logistic costs carried out by trade-off services that favor business actors while still taking into account aspects of the public health/safety protection as well as local business competitiveness". The effectiveness of policy implementation can be accomplished by striving measurable trade-off which is always maintaining service and supervision in balance; revitalizing implementation of single risk management integration; accelerating draft of derivative regulations; optimizing the functions of intelligence; performing joint training and sharing knowledge on a regular and leveled basis.Keywords: Narrative Policy Analysis, Indonesian-FDA, DGCE, dwelling time, logistic costÂ ABSTRAK:Paket Kebijakan Ekonomi XV telah memunculkan kesenjangan antara tugas pengawasan dan kemudahan melakukan usaha. Kajian ini bertujuan untuk mengetahui perbedaan narasi yang terjadi dalam implementasi Paket Kebijakan Ekonomi XV khususnya dalam penyederhanaan tata niaga impor, dan menganalisa perubahan stategis dalam bisnis proses pengawasan Obat dan Makanan. Narative Policy Analysis (NPA) pada kajian ini digunakan untuk menganalisa pada level meso (kelompok/organisasi) dengan wawancara pada Petugas BPOM dan DJBC. Fokus kajian adalah pada narasi Presiden Republik Indonesia serta respon Petugas BPOM dan DJBC yang berperan dalam pelaksanaan pengawasan. Metanarasi yang muncul sebagai analisa solusi yakni â€œupaya untuk mengurangi dwelling time dan logistic cost dilakukan dengan trade off pelayanan yang berpihak pada pelaku usaha sekaligus tetap memperhitungkan aspek proteksi kesehatan/keamanan masyarakat serta daya saing usaha lokalâ€. Efektifitas implementasi kebijakan dapat diwujudkan dengan mengupayakan trade-off terukur untuk selalu menjaga keseimbangan antara pelayanan dan pengawasan; revitalisasi penerapan integrasi single risk management; mempercepat penyusunan peraturan turunan; optimalisasi fungsi intelijen; melakukan joint training dan sharing knowledge secara berkala dan berjenjang.Kata Kunci: Narrative Policy Analysis, BPOM, DJBC, dwelling time, logistic costÂ